THE EFFECT OF PRODUCT FASCINATION, SERVICE FASCINATION, AND COMPETITIVE POWER OF TARIFF ON CUSTOMER SATISFACTION AND IMPACT ON TRANSACTION DECISIONS (Study on Agent BRILink BRI Branch of Pati) - Kurniawan, Rizal Mahdi; Soesanto, Harry; Sugiarto, Sugiarto (Master of Management Diponegoro University, 2018)
Bank Rakyat Indonesia (BRI) innovates to launch BRILink Agent services as a collaborative partner between BRI Bank and its customers. The problem in this research is how to improve customer satisfaction which will influence the decisions of transactions at BRILink BRI Branch of Pati. Data on observed variables were obtained through interviews with questionnaires to 110 BRI Bank customers who transacted at BRILink Branch of Pati and tested using AMOS statistic software. The result of SEM analysis confirm the criteria of Goodness of fit that is Chi-Square is 154.616 with probability equal to 0.277; CMIN/DF (1.066); GFI (0.873); AGFI (0.833); TLI (0.991); CFI (0.992); and RMSEA (0.025). The result of hypothesis testing is: transaction decisions are statistically proven to be affected by customer satisfaction, customer satisfaction is statistically proven to be affected by service attractiveness and tariff competitiveness, while the attractiveness of unpaid products has a significant effect.Â